Enfermedad de Wilson: de la clínica a la genética - Lobos U., Rafael; Pardo V., Rosa (Revista Hospital Clínico Universidad de Chile, 2024)
Wilson’s disease is a rare, autosomal recessive disorder caused by excess copper stored in the body. Mutations in the ATP7B gene are associated with Wilson’s Disease. It encodes the ATP7B protein responsible for maintaining normal levels of systemic copper. Intracellular copper overload leads to stress and subsequent oxidative damage to cellular proteins, lipids, DNA, RNA and mitochondria. Wilson’s disease has a wide clinical spectrum, mainly affecting the liver, nervous system, eye and mental health. The diagnosis requires clinical, biochemical, histological and genetic criteria. Treatment should be started early and if followed properly it can prevent clinical deterioration and improve life expectancy and quality of life. Treatment includes dietary measures, pharmacological treatments such as copper chelators and zinc salts, and in certain cases, liver transplantation. Some gene therapies are in the clinical trial phase and could become curative treatments for this disease.